Lebah Madu Dalam Karya Batik Lukis Dan Sulam - Dini Sritika; Eliya Pebriyeni (Lembaga Pengembangan Kinerja Dosen, 2023)
The purpose of making this final work is to create a work of art of batik painting and embroidery whose idea comes from the life of honey bees that can be exemplified by humans in everyday life. The method of creation in this final work is carried out in stages, starting from the preparatory stage of observing phenomena that occur directly, then elaboration (the stage of exploring), the synthesis stage (the creation of ideas), then the realization of the concept of preparing maps, materials, tools, and the process of working on the work. Finally, the completion or finishing stage of the work. All works use the methods of written batik and embroidery. Each work has a different size, based on the theme of nature conservation with the idea of honey bee life in everyday life with the titles,